Dispersal, dormancy, life history and breeding systems of southern African Asteraceae : risk-reducing strategies in unpredictable environments - De Waal, Caroli (Stellenbosch : Stellenbosch University, 2015)
Thesis (PhD)--Stellenbosch University, 2015.